A preparation method and application of carbonized foam layered sulfide negative electrode material
By doping Mo, C, N on ReS2 and growing on the three-dimensional carbonized foam skeleton, the Mo-ReS2@C/CF composite material is formed, and the layered sulfide is easily powdered and the conductivity is low during the charging and discharge process. The problem of improving the rate performance and cycle stability of sodium and potassium ion batteries.
Patent Information
- Application Number
- CN202411398453.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-10-09
AI Technical Summary
Laminated sulfides such as ReS2 are easily powdered during charging and discharge, and have low conductivity, resulting in low rate performance and poor cycle stability of sodium ion batteries and potassium ion batteries.
The Mo source and surfactant polyvinylpyrrolidone (PVP) were added to the system by hydrothermal method, and Mo, C, and N were doped onto ReS2, so that it grew densely and uniformly on the flexible three-dimensional carbonized foam (CF) skeleton to form a The Mo-ReS2@C/CF composite material with good conductivity avoids the use of conductive agents and binders, and improves the electronic conductivity and structural stability of the material.
The rate performance, cycle stability and reversible capacity of the electrode material are improved, and excellent sodium or potassium storage performance is shown, which enhances the electrochemical performance of sodium and potassium ion batteries.
Smart Images

Figure CN118929765B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ion battery negative electrode materials, and in particular to a preparation method and application of a carbonized foam layered sulfide negative electrode material. Background Art
[0002] As the price of lithium carbonate rises, the application of lithium-ion batteries (LIBs) in large-scale stationary energy storage is limited. The physical and chemical properties of sodium-ion batteries (SIBs) and potassium-ion batteries (KIBs) are similar to those of lithium, and the principles of electrochemical reactions are similar. At the same time, their low cost, wide distribution of resources, and high reserves make them promising candidate batteries for large-scale energy storage systems. The characteristics of negative electrode materials directly affect the performance of ion batteries, such as rate performance and cycle life. Due to the large relative atomic mass of sodium and potassium, the energy density is lower than that of LIBs. At present, sodium-ion batteries (SIBs) and potassium-ion batteries (KIBs) generally have problems such as low rate performance and poor cycle stability. Therefore, the development of electrode materials with good performance is crucial to achieve high-performance SIBs and KIBs, which will help improve the performance of energy storage devices and promote the further development of renewable energy storage and utilization. Therefore, the development of new materials or research on electrochemical reactions for new secondary batteries is crucial to improving battery performance.
[0003] Compared with organic materials and carbon materials, transition metal-based composites have more suitable performance in terms of specific capacity and voltage window. Since the MS bond in transition metal sulfides (TMDs) is weaker than the MO bond (M is a transition metal), it is kinetically easier to react with Na + , K + Reaction. ReS2 is an emerging material of transition metal sulfides with a layered structure. Its large interlayer spacing of 0.61 nm, weak interlayer van der Waals forces, and weak coupling of ReS2 multilayer films enable it to have a high sodium or potassium storage capacity. However, ReS2 is prone to pulverization, low conductivity, and rapid capacity decay during the charge and discharge process, which seriously restricts its application in SIBs and KIBs. Studies have shown that regulating the inherent structure of the material at the atomic level to improve its interlayer spacing and conductivity is an effective strategy to enhance its electrochemical performance.
[0004] Carbon materials are widely used in the field of energy storage due to their low cost, environmental friendliness, and easy recycling. However, carbon-based materials also have problems such as slow diffusion rate, insufficient active sites, low rate performance and energy density. At the same time, traditional electrode preparation methods require the addition of binders and conductive agents to load them onto the current collector because most of the active substances are powders. Therefore, the active substance content is low and it is easy to agglomerate, which in turn affects the electrochemical performance of the battery.
[0005] Therefore, solving the problems of easy structural pulverization, low electrical conductivity, and rapid capacity decay of layered sulfides such as ReS2 during the charge and discharge process, and improving the rate performance and cycle stability of SIBs and KIBs are technical issues that urgently need to be solved in the negative electrode material and battery industries. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing a carbonized foam layered sulfide negative electrode material and its application, so as to solve the problems of easy pulverization of the structure, low conductivity and rapid capacity decay of sulfides such as ReS2 proposed in the above-mentioned background technology during the charging and discharging process, thereby improving the electrochemical properties of sodium ion batteries (SIBs) and potassium ion batteries (KIBs) such as rate performance and cycle stability.
[0007] To achieve the above object, the present invention provides the following technical solution: a method for preparing a carbonized foam layered sulfide negative electrode material, wherein the carbonized foam (CF) obtained by high-temperature carbonization of the foam is reacted with ammonium perrhenate (NH4ReO4), thiourea (CH4N2S), hydroxylamine hydrochloride (NH2OH·HCl), ammonium molybdate tetrahydrate ((NH4)6Mo7O 24 ·4H2O), polyvinyl pyrrolidone (PVP), and deionized water are mixed to undergo hydrothermal reaction to obtain Mo-ReS2@PVP / CF composite material, and then the Mo-ReS2@PVP / CF composite material is placed in a tubular furnace for high-temperature carbonization to obtain carbonized foam flexible self-supporting layered sulfide negative electrode material Mo-ReS2@C / CF. The specific process steps are as follows:
[0008] Step 1, preparation of carbonized foam: place the melamine foam in a deionized water ultrasonic cleaner for cleaning for 25 to 30 minutes, then transfer it to an ethanol ultrasonic cleaner for cleaning for 20 to 25 minutes, dry the cleaned melamine foam and place it in a tubular furnace, heat it to 500 to 800 °C at a heating rate of 5 °C / min under an inert gas atmosphere, maintain it for 2 to 2.5 hours, and obtain carbonized foam by cooling.
[0009] Step 2, preparation of Mo-ReS2@PVP / CF composite material: weigh 1.1-1.2 parts by weight of ammonium perrhenate, 1.3-1.4 parts by weight of thiourea, 0.8-0.9 parts by weight of hydroxylamine hydrochloride, 0.3-0.4 parts by weight of ammonium molybdate tetrahydrate, 0.3-0.4 parts by weight of polyvinyl pyrrolidone, and 195-200 parts by weight of deionized water, and stir for 15-18 min to obtain a uniformly dispersed precursor solution, add 30-32 pieces of carbonized foam to the precursor solution, continue stirring for 30-40 min to mix evenly, and then transfer the mixed solution to a polytetrafluoroethylene reaction liner, and then place it in a stainless steel reactor, keep it warm in a forced air drying oven at 210-220°C for 16-18 h, then cool it naturally, and wash it with deionized water and ethanol three times, centrifuge it, and then dry it in a vacuum drying oven at 70-75°C for 8-10 h, and cooled to room temperature to obtain Mo-ReS2@PVP / CF composite material.
[0010] Step 3. Preparation of negative electrode material Mo-ReS2@C / CF: Place the Mo-ReS2@PVP / CF composite material prepared in step 2 in a tubular furnace, heat it to 700-710°C at a heating rate of 5°C / min under an inert gas atmosphere, and maintain it for 2.0h for high-temperature carbonization. After cooling, the negative electrode material Mo-ReS2@C / CF is obtained.
[0011] Furthermore, the carbonized foamed layered sulfide negative electrode material is used in ion batteries.
[0012] Furthermore, the ion battery is prepared by the following method: a CR2032 type battery shell is selected, and the negative electrode shell, spring, gasket, reference electrode-metal sheet, diaphragm, flexible self-supporting Mo-ReS2@C / CF electrode, and positive electrode shell are assembled layer by layer in a specific order, and 0.1 to 0.5 mL of sodium ion battery electrolyte or potassium ion battery electrolyte is added dropwise, and the battery is placed in a packaging machine for pressing to obtain a sodium ion battery or a potassium ion battery.
[0013] As a preferred technical solution of the present invention, the length, width and height of the melamine foam are 1.5-2 cm, 1.5-2 cm and 0.3-0.5 cm respectively.
[0014] As a preferred technical solution of the present invention, the frequency of the ultrasonic cleaning machine is 100-120 Hz, and the ethanol concentration is 95%.
[0015] As a preferred technical solution of the present invention, the inert gas is nitrogen or argon, and the standard concentration of nitrogen or argon is 99.99%.
[0016] As a preferred technical solution of the present invention, the sodium ion battery electrolyte is composed of sodium perchlorate (NaClO4), ethylene carbonate (EC), diethyl carbonate (DEC), and fluoroethylene carbonate (FEC), the concentration of sodium perchlorate is 1-1.2 mol / L, the weight ratio of ethylene carbonate to diethyl carbonate is 1:1, and the concentration of fluoroethylene carbonate is 5-5.5%.
[0017] As a preferred technical solution of the present invention, the potassium ion battery electrolyte is composed of potassium fluorosilicate (KFSI), ethylene carbonate (EC), and diethyl carbonate (DEC), the concentration of potassium fluorosilicate is 0.8-0.9 mol / L, and the weight ratio of ethylene carbonate to diethyl carbonate is 1:1.
[0018] As a preferred technical solution of the present invention, the metal sheet is a 12mm metal sodium sheet or metal potassium sheet.
[0019] As a preferred technical solution of the present invention, the ion battery preparation is carried out in a water-free and oxygen-free glove box, and the water and oxygen concentrations in the glove box are H2O<0.01ppm and O2<0.01ppm.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] 1. The present invention uses Re as the research object of layered sulfide, adds cations represented by Mo source, surfactant polyvinyl pyrrolidone (PVP) and three-dimensional carbonized foam (CF) into the system by hydrothermal method, and uniformly dopes Mo, C and N into ReS2, so that it grows densely and uniformly on the flexible three-dimensional carbonized foam (CF) skeleton, and obtains Mo-ReS2@C / CF composite material with good conductivity, rich active sites and stable structure. In the Mo-ReS2@C / CF composite material, the introduction of Mo effectively changes the structure of ReS2 material at the atomic level, and then introduces C and N into ReS2 "from bottom to top" by introducing PVP and then carbonizing, forming a multi-doped layered sulfide. The simultaneous introduction of anions and cations synergistically improves the electronic conductivity of the material, thereby improving the rate performance of the electrode material in ion batteries with large ion radius.
[0022] 2. As a self-supporting conductive current collector, the three-dimensional carbonized foam avoids the use of conductive agents, binders and current collectors, effectively improving the energy density of the material. The flexibility of its three-dimensional structure can not only effectively alleviate the volume expansion of active materials such as layered sulfides, but also broaden the application scenarios of electrode materials, and is expected to be used in flexible wearable devices. The in-situ and tight growth of layered transition metal sulfides on carbonized foam is more conducive to the transmission of ions and electrons, effectively alleviating the problems of sulfide shedding and pulverization during charging and discharging, and further improving the cycle stability of the material. Based on the synergistic effect of materials and structures, the electrochemical properties of Mo-ReS2@C / CF negative electrode materials such as rate performance, cycle stability, and reversible capacity have been effectively improved, showing excellent sodium or potassium storage performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 SEM images of carbonized foam (CF) of melamine foam in the present invention at a, b) 500°C, c, d) 600°C, e, f) 700°C, g, h) 800°C, and i) XRD graph;
[0024] Figure 2 SEM images of ReS2, Mo-ReS2@C, and Mo-ReS2@C / CF in the present invention;
[0025] Figure 3 XRD diagrams of ReS2, Mo-ReS2@C, and Mo-ReS2@C / CF in the present invention;
[0026] Figure 4 TEM image of Mo-ReS2@C / CF in the present invention;
[0027] Figure 5 This is the EDS image of Mo-ReS2@C / CF in the present invention;
[0028] Figure 6 Raman spectra of ReS2, Mo-ReS2@C, and Mo-ReS2@C / CF in the present invention;
[0029] Figure 7 This is the XPS graph of Mo-ReS2@C / CF in the present invention;
[0030] Figure 8 The discharge cycle curves of sodium ion batteries of ReS2, Mo-ReS2, ReS2@C and Mo-ReS2@C in the present invention at current densities of 0.05, 0.1, 0.2, 0.5 and 1 A / g;
[0031] Fig. 9The discharge cycle curves of sodium ion batteries of ReS2, Mo-ReS2@C, and Mo-ReS2@C / CF in the present invention at current densities of 0.05, 0.1, 0.2, 0.5, and 1 A / g;
[0032] Fig.10 The discharge cycle curves of sodium ion batteries of ReS2, Mo-ReS2@C, and Mo-ReS2@C / CF in the present invention at a current density of 1A / g;
[0033] Fig.11 The charge and discharge curves of ReS2, Mo-ReS2@C, and Mo-ReS2@C / CF in the present invention after 1, 2, 7, 10, 20, and 50 cycles at a current density of 1A / g in a sodium ion battery;
[0034] Fig.12 EIS graphs of ReS2, Mo-ReS2@C, and Mo-ReS2@C / CF in the present invention after 1, 2, 7, 10, 20, and 50 cycles at a current density of 1 A / g in a sodium ion battery;
[0035] Fig.13 The cyclic voltammetry curves of Mo-ReS2@C / CF in the present invention at the scanning rates of 0.1, 0.2, 0.4, 0.8 and 1 mV / s in sodium ion battery;
[0036] Fig.14 This is a graph of the capacitance contribution ratio of Mo-ReS2@C / CF in the sodium ion battery of the present invention at scan rates of 0.1, 0.2, 0.4, 0.8, and 1 mV / s;
[0037] Fig.15 The discharge cycle curves of ReS2, Mo-ReS2@C, and Mo-ReS2@C / CF potassium ion batteries in the present invention at 0.05, 0.1, 0.2, 0.5, and 1 A / g;
[0038] Fig.16 The discharge cycle curves of potassium ion batteries of ReS2, Mo-ReS2@C, and Mo-ReS2@C / CF in the present invention at a current density of 0.5A / g;
[0039] Fig.17 The present invention is a flow chart for preparing the carbonized foam flexible self-supporting layered sulfide negative electrode material. DETAILED DESCRIPTION
[0040] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] Carbonized foam is a three-dimensional flexible substrate with low price, strong structural stability, large specific surface area and good conductivity. It can be compounded with other nanomaterials to build an effective conductive network, improve the electronic conductivity of electrode materials, and ensure the rapid diffusion of ions or electrons. At the same time, carbonized foam has strong structural stability, and it is not easy to pulverize or break during the charge and discharge cycle, preventing the electrode material from being destroyed during the charge and discharge process. In addition, the carbonized foam has a large specific surface area, which can increase the adsorption capacity of the material surface and further improve the electrochemical performance of the composite material. The layered sulfide is directly combined with the carbonized foam substrate with good conductivity by a hydrothermal method, avoiding the use of conductive agents and binders. The direct contact between the layered sulfide and the carbonized foam current collector is also more conducive to the transmission of ions and electrons. The layered sulfide grows directly on the carbonized foam conductive substrate, and the layered sulfide and carbonized foam are closely combined, which further alleviates the problems of active material shedding caused by volume expansion during the charge and discharge process.
[0042] In view of the problem that ReS2 is easy to pulverize and has low conductivity during the charging and discharging process, the present invention uses Re as the research object of layered sulfide, adds Mo source, surfactant polyvinyl pyrrolidone (PVP) and three-dimensional carbonized foam (CF) to the system by hydrothermal method, and dopes Mo, N and C into ReS2, so that it grows densely and evenly on the flexible three-dimensional carbonized foam (CF) skeleton, and obtains Mo-ReS2@C / CF composite materials with good conductivity, rich active sites and stable structure. Starting from the basic units at the atomic and molecular levels, the present invention constructs materials with specific structures and functions through chemical methods, that is, in the Mo-ReS2@C / CF composite material, Mo, C and N are introduced "from bottom to top", which effectively changes the structure of ReS2 material at the atomic level, forms multi-doped layered sulfides, improves the electronic conductivity of the material, and thus improves the rate performance of the electrode material.
[0043] As a self-supporting conductive current collector, the three-dimensional carbonized foam avoids the use of conductive agents, binders and current collectors, effectively improving the energy density of the material. The flexibility of its three-dimensional structure can not only effectively alleviate the volume expansion of the active material itself, but also broaden the application scenarios of the electrode material, and is expected to be used in flexible wearable devices. The in-situ close growth of layered transition metal sulfides on the carbonized foam is more conducive to the transmission of ions and electrons, effectively alleviating the problems of sulfide shedding and pulverization during the charging and discharging process, and further improving the cycle stability of the material. Based on the synergistic effect of materials and structures, the electrochemical properties of the Mo-ReS2@C / CF negative electrode material, such as rate performance, cycle stability, and reversible capacity, have been effectively improved, showing excellent sodium or potassium storage performance.
[0044] The raw materials used in the present invention are all commercially available raw materials. Embodiment 1:
[0045] A method for preparing a carbonized foam layered sulfide negative electrode material, the specific process steps are:
[0046] Step 1. Preparation of carbonized foam: Place melamine foam (length, width and height are 1.5 cm, 1.5 cm and 0.3 cm respectively) in a deionized water ultrasonic cleaner for cleaning for 25 min, then transfer to an ethanol ultrasonic cleaner for cleaning for 20 min, dry the cleaned melamine foam and place it in a tubular furnace, heat it to 700 °C at a heating rate of 5 °C / min under a nitrogen atmosphere and maintain it for 2 hours for high-temperature carbonization treatment, and cool it to obtain carbonized foam. The frequency of the ultrasonic cleaner is 100-120 Hz, and the ethanol concentration is 95%.
[0047] Step 2, preparation of Mo-ReS2@PVP / CF composite material: weigh 1.1 parts by weight of ammonium perrhenate, 1.3 parts by weight of thiourea, 0.8 parts by weight of hydroxylamine hydrochloride, 0.3 parts by weight of ammonium molybdate tetrahydrate, 0.3 parts by weight of polyvinyl pyrrolidone, and 195 parts by weight of deionized water, mix and stir for 18 min to obtain a uniformly dispersed precursor solution, add 30 pieces of carbonized foam to the precursor solution and continue to stir for 30 minutes to mix evenly, then transfer the mixed solution to a reactor, carry out hydrothermal reaction in a forced air drying oven at 220°C for 18 h, then cool naturally, and after three centrifugations, deionized water washing and ethanol washing, place in a vacuum drying oven at 70°C and dry for 8 h, and cool to room temperature to obtain the Mo-ReS2@PVP / CF composite material.
[0048] Step 3. Preparation of negative electrode material Mo-ReS2@C / CF: Place the Mo-ReS2@PVP / CF composite material prepared in step 2 in a tubular furnace, heat it to 700°C at a heating rate of 5°C / min under a nitrogen atmosphere, and then maintain it for 2.0 h for high-temperature carbonization. After cooling, the negative electrode material Mo-ReS2@C / CF is obtained.
[0049] The sodium ion battery is prepared by the following method:
[0050] A CR2032 battery shell was selected, and the negative electrode shell, shrapnel, gasket, reference electrode-12mm metal sodium sheet, diaphragm, flexible self-supporting Mo-ReS2@C / CF electrode, and positive electrode shell were assembled layer by layer in a specific order. After 0.2 mL of sodium ion battery electrolyte was added, the battery was placed in a packaging machine for pressing to obtain a sodium ion battery. The sodium ion battery electrolyte consisted of sodium perchlorate, ethylene carbonate, diethyl carbonate, and fluoroethylene carbonate. The concentration of sodium perchlorate was 1 mol / L, the weight ratio of ethylene carbonate to diethyl carbonate was 1:1, and the concentration of fluoroethylene carbonate was 5%. The preparation of the sodium ion battery was carried out in an anhydrous and oxygen-free glove box, and the water and oxygen concentrations in the glove box were H2O<0.01ppm and O2<0.01ppm. Embodiment 2:
[0051] On the basis of Example 1, the negative electrode material Mo-ReS2@C / CF prepared in Example 1 was made into a potassium ion battery, and the potassium ion battery was prepared by the following method:
[0052] A CR2032 battery shell was selected, and the negative electrode shell, spring, gasket, reference electrode-12mm metal potassium sheet, diaphragm, flexible self-supporting Mo-ReS2@C / CF electrode, and positive electrode shell were assembled layer by layer in a specific order. After 0.2 mL of potassium ion battery electrolyte was added, it was placed in a packaging machine for pressing to obtain a potassium ion battery. The potassium ion battery electrolyte consisted of potassium fluorosilicate, ethylene carbonate, and diethyl carbonate. The concentration of potassium fluorosilicate was 0.8 mol / L, and the weight ratio of ethylene carbonate to diethyl carbonate was 1:1.
[0053] Other method steps are the same as those in Example 1.
[0054] Comparative Example 1:
[0055] The preparation method of the sulfide negative electrode material is as follows: ammonium perrhenate (NH4ReO4), thiourea (CH4N2S), hydroxylamine hydrochloride (NH2OH·HCl), and deionized water are mixed for hydrothermal reaction to obtain ReS2 powder. The specific process method is as follows: 1.1 parts by weight of ammonium perrhenate, 1.3 parts by weight of thiourea, 0.8 parts by weight of hydroxylamine hydrochloride, and 195 parts by weight of deionized water are weighed and mixed for 18 minutes, and then the mixed solution is transferred to a reactor, and the mixture is subjected to hydrothermal reaction in a 220°C forced air drying oven for 18 hours, and then naturally cooled, and then washed with deionized water three times, washed with ethanol, and centrifuged, and then dried in a vacuum drying oven at 70°C for 8 hours, and then cooled to room temperature to obtain the sulfide negative electrode material ReS2 powder, and the ethanol concentration is 95%.
[0056] The sodium ion battery is prepared by the following method:
[0057] S1. Preparation of electrode materials: ReS2 powder and carbon black conductive agent were weighed according to the mass ratio and ground in a mortar for 25 minutes. A certain proportion of polyvinylidene fluoride (PVDF) binder was added and mixed and ground for 30 minutes to obtain a premixed material. Finally, 0.5% of the total mass of the premixed material was added with N-methylpyrrolidone (NMP), and the mixture was transferred to a revolution and rotation mixer and continued to be ground for 40 minutes. The revolution speed of the revolution and rotation speed of the revolution and rotation mixer was 600 r / min and 420 r / min. The ground slurry was evenly coated on a copper foil. The copper foil was transferred to a glass plate and fixed, and then placed in a vacuum drying oven at 80-82 °C for 12 hours to obtain an electrode sheet, in which ReS2 powder, carbon black conductive agent and polyvinylidene fluoride (PVDF) were composed of a mass ratio of 7:2:1.
[0058] S2. Preparation of sodium ion battery: select CR2032 type battery shell, assemble the negative electrode shell, spring, gasket, reference electrode-12mm metal sodium sheet, diaphragm, electrode sheet, and positive electrode shell layer by layer in a specific order, and then put them into the packaging machine for pressing to obtain a sodium ion battery. The preparation of sodium ion battery is carried out in a water-free and oxygen-free glove box. The water and oxygen concentrations in the glove box are H2O<0.01ppm and O2<0.01ppm.
[0059] Comparative Example 2:
[0060] On the basis of comparative example 1, the ReS2 powder prepared in comparative example 1 was made into a potassium ion battery. The preparation method of the potassium ion battery was as follows: a CR2032 battery shell was selected, and the negative electrode shell, shrapnel, gasket, reference electrode-12mm metal potassium sheet, diaphragm, electrode sheet, and positive electrode shell were assembled layer by layer in a specific order and then placed in a packaging machine for pressing to obtain a potassium ion battery. The preparation of the potassium ion battery was carried out in an anhydrous and oxygen-free glove box, and the water and oxygen concentrations in the glove box were H2O<0.01ppm and O2<0.01ppm.
[0061] The other method steps are the same as those in Comparative Example 1.
[0062] Comparative Example 3:
[0063] During the preparation of ReS2 solution, ammonium molybdate tetrahydrate ((NH4)6Mo7O 24 ·4H2O), the specific process steps are:
[0064] Preparation of Mo-ReS2 composite material: Weigh 1.1 parts by weight of ammonium perrhenate, 1.3 parts by weight of thiourea, 0.8 parts by weight of hydroxylamine hydrochloride, 0.3 parts by weight of ammonium molybdate tetrahydrate, and 195 parts by weight of deionized water, mix and stir for 18 min to obtain a uniformly dispersed precursor solution, and then transfer the mixed solution to a reactor, carry out hydrothermal reaction in a forced air drying oven at 220°C for 18 h, and then cool naturally. After washing with deionized water three times, washing with ethanol, and centrifuging, the solution is placed in a vacuum drying oven at 70°C and dried for 8 h. The solution is cooled to room temperature to obtain Mo-ReS2 powder with an ethanol concentration of 95%.
[0065] Sodium ion batteries are prepared using the following method:
[0066] S1. Preparation of electrode materials: Mo-ReS2 powder and carbon black conductive agent were weighed according to the mass ratio and ground in a mortar for 25 min. A certain proportion of polyvinylidene fluoride (PVDF) binder was added and mixed and ground for 30 min to obtain a premixed material. Finally, 0.5% of the total mass of the premixed material was added with N-methylpyrrolidone (NMP), and the mixture was transferred to a revolution and rotation mixer and continued to be ground for 40 min. The revolution speed of the revolution and rotation speed of the revolution and rotation mixer was 600 r / min and 420 r / min. The ground slurry was evenly coated on a copper foil. The copper foil was transferred to a glass plate and fixed, and then placed in a vacuum drying oven at 80-82 °C for drying for 12 h to obtain an electrode sheet, in which Mo-ReS2 powder, carbon black conductive agent and polyvinylidene fluoride (PVDF) were composed of a mass ratio of 7:2:1.
[0067] S2. Preparation of sodium ion battery: select CR2032 type battery shell, assemble the negative electrode shell, spring, gasket, reference electrode-12mm metal sodium sheet, diaphragm, electrode sheet, and positive electrode shell layer by layer in a specific order, and then put them into the packaging machine for pressing to obtain a sodium ion battery. The preparation of sodium ion battery is carried out in a water-free and oxygen-free glove box. The water and oxygen concentrations in the glove box are H2O<0.01ppm and O2<0.01ppm.
[0068] Comparative Example 4:
[0069] Polyvinyl pyrrolidone (PVP) is added during the preparation of ReS2 solution. The specific process steps are as follows:
[0070] Step 1, preparation of ReS2@PVP composite material: weigh 1.1 parts by weight of ammonium perrhenate, 1.3 parts by weight of thiourea, 0.8 parts by weight of hydroxylamine hydrochloride, 0.3 parts by weight of polyvinyl pyrrolidone, and 195 parts by weight of deionized water, mix and stir for 18 min to obtain a uniformly dispersed precursor solution, and then transfer the mixed solution to a reactor, carry out hydrothermal reaction in a forced air drying oven at 220°C for 18 h, and then cool naturally, and then wash with deionized water 3 times, wash with ethanol, and centrifuge, and then place at 70°C, dry in a vacuum drying oven for 8 h, and cool to room temperature to obtain a ReS2@PVP composite material with an ethanol concentration of 95%.
[0071] Step 2. Preparation of negative electrode material ReS2@C: Place the ReS2@PVP composite material prepared in step 2 in a tubular furnace, and in a nitrogen atmosphere, heat it to 700°C at a heating rate of 5°C / min, then keep it for 2.0 h and then keep it for 2.0 h for high-temperature carbonization. After cooling, obtain the negative electrode material ReS2@C powder.
[0072] Sodium ion batteries are prepared using the following method:
[0073] S1. Preparation of electrode materials: ReS2@C powder and carbon black conductive agent were weighed according to the mass ratio and ground in a mortar for 25 min. A certain proportion of polyvinylidene fluoride (PVDF) binder was added and mixed and ground for 30 min to obtain a premixed material. Finally, 0.5% of the total mass of the premixed material was added with N-methylpyrrolidone (NMP), and the mixture was transferred to a revolution and rotation mixer and continued to be ground for 40 min. The revolution speed of the revolution and rotation speed of the revolution and rotation mixer was 600 r / min and 420 r / min. The ground slurry was evenly coated on a copper foil. The copper foil was transferred to a glass plate and fixed, and then placed in a vacuum drying oven at 80-82 °C for 12 h to obtain an electrode sheet, in which ReS2@C powder, carbon black conductive agent and polyvinylidene fluoride (PVDF) were composed of a mass ratio of 7:2:1.
[0074] S2. Preparation of sodium ion battery: select CR2032 type battery shell, assemble the negative electrode shell, spring, gasket, reference electrode-12mm metal sodium sheet, diaphragm, electrode sheet, and positive electrode shell layer by layer in a specific order, and then put them into the packaging machine for pressing to obtain a sodium ion battery. The preparation of sodium ion battery is carried out in a water-free and oxygen-free glove box. The water and oxygen concentrations in the glove box are H2O<0.01ppm and O2<0.01ppm.
[0075] Comparative Example 5:
[0076] During the preparation of ReS2 solution, ammonium molybdate tetrahydrate ((NH4)6Mo7O 244H2O), polyvinyl pyrrolidone (PVP), the specific process steps are:
[0077] Step 1, preparation of Mo-ReS2@PVP composite material: weigh 1.1 parts by weight of ammonium perrhenate, 1.3 parts by weight of thiourea, 0.8 parts by weight of hydroxylamine hydrochloride, 0.3 parts by weight of ammonium molybdate tetrahydrate, 0.3 parts by weight of polyvinyl pyrrolidone, and 195 parts by weight of deionized water, mix and stir for 18 min to obtain a uniformly dispersed precursor solution, and then transfer the mixed solution to a reactor, carry out hydrothermal reaction in a forced air drying oven at 220°C for 18 h, and then cool naturally, and then wash with deionized water 3 times, wash with ethanol, and centrifuge, and then place at 70°C, dry in a vacuum drying oven for 8 h, and cool to room temperature to obtain a Mo-ReS2@PVP composite material with an ethanol concentration of 95%.
[0078] Step 2. Preparation of negative electrode material Mo-ReS2@C: Place the Mo-ReS2@PVP composite material prepared in step 2 in a tubular furnace, and in a nitrogen atmosphere, heat it to 700°C at a heating rate of 5°C / min, then keep it for 2.0 h and then keep it for 2.0 h for high-temperature carbonization. After cooling, obtain the negative electrode material Mo-ReS2@C powder.
[0079] Sodium ion batteries are prepared using the following method:
[0080] S1. Preparation of electrode materials: Mo-ReS2@C powder and carbon black conductive agent were weighed according to the mass ratio and ground in a mortar for 25 min. A certain proportion of polyvinylidene fluoride (PVDF) binder was added and mixed and ground for 30 min to obtain a premixed material. Finally, 0.5% of the total mass of the premixed material was added with N-methylpyrrolidone (NMP), and the mixture was transferred to a revolution and rotation mixer and continued to be ground for 40 min. The revolution speed of the revolution and rotation speed of the revolution and rotation mixer was 600 r / min and 420 r / min. The ground slurry was evenly coated on a copper foil. The copper foil was transferred to a glass plate and fixed, and then placed in a vacuum drying oven at 80-82 °C for drying for 12 h to obtain an electrode sheet, in which Mo-ReS2@C powder, carbon black conductive agent and polyvinylidene fluoride (PVDF) were composed of a mass ratio of 7:2:1.
[0081] S2. Preparation of sodium ion battery: select CR2032 type battery shell, assemble the negative electrode shell, spring, gasket, reference electrode-12mm metal sodium sheet, diaphragm, electrode sheet, and positive electrode shell layer by layer in a specific order, and then put them into the packaging machine for pressing to obtain a sodium ion battery. The preparation of sodium ion battery is carried out in a water-free and oxygen-free glove box. The water and oxygen concentrations in the glove box are H2O<0.01ppm and O2<0.01ppm.
[0082] Comparative Example 6:
[0083] On the basis of comparative example 5, the Mo-ReS2@C powder prepared in comparative example 5 was made into a potassium ion battery. The preparation method of the potassium ion battery was as follows: a CR2032 battery shell was selected, and the negative electrode shell, shrapnel, gasket, reference electrode-12mm metal potassium sheet, diaphragm, electrode sheet, and positive electrode shell were assembled layer by layer in a specific order and then placed in a packaging machine for pressing to obtain a potassium ion battery. The preparation of the potassium ion battery was carried out in an anhydrous and oxygen-free glove box, and the water and oxygen concentrations in the glove box were H2O<0.01ppm and O2<0.01ppm.
[0084] The other method steps are the same as those in Comparative Example 5.
[0085] Melamine foam (length, width and height are 1.5 cm, 1.5 cm and 0.3 cm respectively) was carbonized at 500℃, 600℃, 700℃ and 800℃ to obtain carbonized foam (CF). The structure of the material was determined by scanning electron microscopy (SEM) and the composition and crystal structure of the material were determined by X-ray diffraction (XRD). The results are shown in Figure 1 , from the surface of CF, it can be seen that the surface of CF is smooth and has a three-dimensional structure. After sintering and carbonizing melamine foam under different temperature conditions, it can still maintain a three-dimensional network structure. 1 i) is the XRD of carbonized foam under four temperature conditions. The foam carbonized at different temperatures is basically the same in XRD. XRD proves that CF has a good match with the standard card (JCPDS No. 26-1077), indicating that melamine foam can be carbonized under four temperature conditions.
[0086] The ReS2 prepared in comparative example 1, the Mo-ReS2@C prepared in comparative example 5, and the Mo-ReS2@C / CF prepared in example 1 were subjected to scanning electron microscopy (SEM) scanning and X-ray diffraction (XRD) analysis. Figure 2 and Figure 3 As shown, Figure 2 SEM images of ReS2, Mo-ReS2@C, and Mo-ReS2@C / CF. Figure 2 Figures a and b in the figure show the morphological characteristics of ReS2 nanosheets prepared by a one-step hydrothermal method. It can be observed from the figure that the prepared ReS2 nanosheets have a thin sheet structure. Figure 2 In Figure a, we can see that these nanosheets form a spherical structure with consistent morphology. Figure 2 From Figure b, it can be observed that the thickness of these nanosheets is relatively small, about 2 to 3 nm, and the width is between 50 and 100 nm. These results indicate that the ReS2 nanosheets prepared by the hydrothermal method have consistent nanosheet morphology and a relatively thin layer structure. Figure 2Figures c and d are SEM images of Mo-ReS2@C. It can be seen that after the introduction of Mo and C in ReS2, Mo-ReS2@C is still a nanosheet ball composed of nanosheets. Figure 2 Figures e and f in the figure are SEM images of Mo-ReS2@C / CF. The interlaced Mo-ReS2@C nanosheets are uniformly and densely grown in situ on the CF surface. Figure 2 From Figure f, we can observe that there are pores of different sizes between the Mo-ReS2@C nanosheets, which can provide more active sites. Figure 3 In the experiment, XRD confirmed the existence of ReS2 phase (JCPDS No. 89-0341).
[0087] The Mo-ReS2@C / CF negative electrode material prepared by the present invention was examined by transmission electron microscopy (TEM) (e.g. Figure 4 ) to observe the internal morphology and use energy dispersive spectroscopy (EDS) to determine the element types (such as Figure 5 ). Figure 4 The TEM of Figure a clearly shows the nanostructure of Mo-ReS2@C composed of thin sheets. This morphology is attributed to the nucleation of ReS2 induced by PVP during the hydrothermal process, and the ReS2 nanosheets grow in all directions in a petal-like manner. Figure 4 The lamellar structure of Mo-ReS2 can be seen more intuitively in the high-resolution transmission electron microscope (HRTEM) in Figure b. The interplanar spacing of 0.61 nm belongs to the (002) crystal plane of the ReS2 crystal. Figure 5 It shows that Re, S, Mo, N and C elements are evenly distributed on the Mo-ReS2@C / CF nanosheet spheres.
[0088] The ReS2 prepared in Comparative Example 1, the Mo-ReS2@C prepared in Comparative Example 5, and the Mo-ReS2@C / CF prepared in Example 1 were subjected to Raman spectroscopy analysis. Figure 6 As shown in the figure, the Raman spectra of ReS2, Mo-ReS2@C, and Mo-ReS2@C / CF are -1 and 210 cm -1 There are two obvious peaks at 1350 cm-1, corresponding to the two main phonon vibration modes in ReS2: in-plane (Eg) and out-of-plane (Ag). For Mo-ReS2@C and Mo-ReS2@C / CF doped with Mo and C, their Raman spectra still retain the characteristic peaks of ReS2, and the peak positions have not changed much, but the peak intensities have changed. This is due to the structural anisotropy of ReS2. -1 The D peak (disordered amorphous carbon) near 1583 cm -1The G peak (crystalline graphite carbon) near the surface of Mo-ReS2@C and Mo-ReS2@C / CF is shown in Figure 2, confirming the successful introduction of C. D / I G The strength ratios are 0.978 and 0.968, respectively, indicating that the graphitization degree of the carbon material is high, and the graphitization degree of Mo-ReS2@C / CF is better than that of Mo-ReS2@C.
[0089] Figure 7 The X-ray photoelectron spectroscopy (XPS) diagram of Mo-ReS2@C / CF shows the full XPS spectrum of Mo-ReS2@C / CF, confirming the presence of elements including C, S, Mo, Re, and N. In the high-resolution XPS spectrum of S 2p ( Figure 7 (b) Two peaks are observed at 163.8 and 162.4 eV, corresponding to the S 2p 1 / 2 and S 2p 3 / 2 ; Figure 7 Figure c shows the Re 4f high-resolution spectrum, where Re 4f 5 / 2 and 4f 7 / 2 The two characteristic peaks of binding energy are located at 44.5 eV and 41.65 eV; Figure 7 Figure d shows the Mo 3d and S 2s spectra. The S 2p and Mo 3d spectra show six peaks at 235.3, 232.55, 231.8, 229.55, 228.75 and 226.6 eV, corresponding to Mo 6+ 3d 3 / 2 、Mo 6+ 3d 5 / 2 、Mo 4+ 3d 3 / 2 、Mo 4+ 3d 5 / 2 and S 2s; Figure 7 Figure e in the figure is the N 1s and Mo 3p spectra, where the characteristic peaks at 400.85 and 398.5 eV correspond to pyrrolic nitrogen and pyridinic nitrogen, and the fitting peak at 395 eV corresponds to Mo 3p; Figure 7 As shown in Figure f, in the C 1s high-resolution spectrum of Mo-ReS2@C / CF, the three groups of fitting peaks located at 287.7, 286.15, and 284.85 eV can be attributed to CO, CN, and CC bonds. It can be clearly seen from the XPS test results that there is an interaction between the CF self-supporting carbon material and the Mo-ReS2@C component in the Mo-ReS2@C / CF composite material.
[0090] Figure 8The discharge cycle curves of sodium ion batteries of ReS2 prepared in comparative example 1, Mo-ReS2 prepared in comparative example 3, ReS2@C prepared in comparative example 4, and Mo-ReS2@C prepared in comparative example 5 at current densities of 0.05, 0.1, 0.2, 0.5, and 1 A / g are shown in FIG. Figure 8 It can be seen that through the introduction of the "bottom-up" atomic level, the synergistic effect of Mo, C and N makes Mo-ReS2@C show better rate performance and cycle stability than ReS2@C, Mo-ReS2 and ReS2.
[0091] Fig. 9 The sodium ion battery discharge cycle curves of the sodium ion batteries prepared in Comparative Example 1 (ReS2), Comparative Example 5 (Mo-ReS2@C), and Example 1 (Mo-ReS2@C / CF) of the present invention at current densities of 0.05, 0.1, 0.2, 0.5, and 1A / g. It can be seen that Mo-ReS2@C / CF exhibits a higher specific capacity than Mo-ReS2@C and ReS2, and the introduction of CF further enhances the comprehensive electrochemical performance of the composite material. At current densities of 0.05, 0.1, 0.2, 0.5, and 1A / g, the capacity of the Mo-ReS2@C / CF electrode can reach 574, 513, 472, 388, and 324 mAh·g, respectively. -1 , at 1A·g -1 The battery continued to cycle for 30 times at a current density of , and the capacity remained basically unchanged, indicating that the material has excellent cycle stability and rate performance.
[0092] Fig.10 The discharge cycle performance of the sodium ion batteries prepared in Comparative Example 1 (ReS2), Comparative Example 5 (Mo-ReS2@C), and Example 1 (Mo-ReS2@C / CF) of the present invention at a current density of 1 A / g. At the same current density, Mo-ReS2@C / CF exhibits a higher capacity. At a current density of 1.0 A / g, Mo-ReS2@C / CF is stably maintained at 400 mAh·g in 900 cycles. -1 , indicating that the material has good cycle stability and the coulombic efficiency is almost maintained at 100%. Compared with Mo-ReS2@C, the good cycle stability of Mo-ReS2@C / CF material can be attributed to the effective inhibition of the volume expansion of the thin-layer sulfide ReS2 material by the CF self-supporting carbon material during the charge and discharge process, and the overall conductivity, rate performance and cycle stability of the material are improved.
[0093] Fig.11The charge and discharge curves of the sodium ion batteries prepared in Example 1 (ReS2), Comparative Example 5 (Mo-ReS2@C) and Example 1 (Mo-ReS2@C / CF) at a current density of 1 A / g after 1, 2, 7, 10, 20 and 50 cycles. Fig.11 In Figure a, the first charge / discharge specific capacity of ReS2 is 403.87 / 563.57 mAh·g -1 The first coulombic efficiency is 71.66%. In the second cycle of charge and discharge, the coulombic efficiency of the electrode quickly rises to 93.56%. However, the discharge specific capacity has a more obvious attenuation in the subsequent cycles, especially after the 20th cycle, the discharge specific capacity of the ReS2 electrode has a more obvious decline, so the cycle stability of the ReS2 electrode is poor. Fig.11 Figure b shows the charge-discharge curves of the Mo-ReS2@C electrode after four different cycles. It can be seen that the charge / discharge specific capacity of the first cycle is 451.24 / 680.25 mAh·g -1 The first coulombic efficiency is 66.32%. In the second cycle of charge and discharge, the coulombic efficiency of the electrode quickly rises to 93.78%. In the subsequent 50 cycles, it can be found that the discharge specific capacity of the Mo-ReS2@C electrode has almost no loss, indicating that the charge and discharge cycle performance of the Mo-ReS2@C electrode is good; the charge and discharge curves of Mo-ReS2@C / CF after four different cycles are shown in Figure 2. Fig.11 As shown in Figure c, the first charge / discharge specific capacity is 666.25 / 1320.16 mAh·g -1 The first coulombic efficiency was 50.46%. During the second cycle of charge and discharge, the coulombic efficiency of the electrode quickly rose to 98.23%. In the subsequent 50 cycles, it was found that the discharge specific capacity of the Mo-ReS2@C / CF electrode had almost no loss, and the conductivity and cycle stability of the Mo-ReS2@C / CF electrode were better than those of Mo-ReS2@C and ReS2.
[0094] Fig.12 The electrochemical impedance spectra (EIS) of the sodium ion batteries prepared in Example 1 (ReS2), Comparative Example 5 (Mo-ReS2@C) and Example 1 (Mo-ReS2@C / CF) of the present invention after 1, 2, 7, 10, 20 and 50 cycles at a current density of 1 A / g are shown in FIG. Fig.12 It can be seen that the internal resistance of Mo-ReS2@C / CF is the smallest, followed by Mo-ReS2@C, and finally ReS2. Fig.12As can be seen from Figure a, the internal resistance of ReS2 is large after the first cycle, and its initial conductivity is very low. In the subsequent 2 to 20 cycles, the ReS2 electrode sheet shows a small resistance. However, at the 50th cycle, it can be found that the resistance of the ReS2 electrode sheet rises sharply, indicating that the stability of the ReS2 electrode sheet is poor. Fig.12 Figure b is the electrochemical impedance spectroscopy diagram of the Mo-ReS2@C electrode after different cycles. It can be seen from the figure that the resistance of the Mo-ReS2@C electrode is lower than that of the ReS2 electrode as a whole, which is attributed to the introduction of Mo and C. Fig.12 In Figure c, the impedance of the Mo-ReS2@C / CF electrode has been in a small range in the first 50 cycles. Thanks to the introduction of carbonized foam, its resistance is much lower than that of ReS2 and Mo-ReS2@C electrodes, which makes it have high conductivity, which is beneficial to the improvement of the electrochemical performance of sodium / potassium ion batteries.
[0095] Fig.13 The cyclic voltammetry curves of Mo-ReS2@C / CF negative electrode materials at scan rates of 0.1, 0.2, 0.4, 0.8, and 1 mV / s for sodium ion batteries are shown in Figure 2. Fig.13 As shown, when the scan rate increases, the CV peak of the Mo-ReS2@C / CF electrode expands outward, which is caused by the electrode polarization at different current densities. The shape of the CV at each scan rate is very similar, which proves that the battery has good cycle stability.
[0096] Fig.14 is the capacitance contribution ratio of Mo-ReS2@C / CF at scan rates of 0.1, 0.2, 0.4, 0.8, and 1 mV / s. With the increase of scan rate, the capacitance contribution rate also increases. -1 At scan rates of 1.0 mV / s, the capacitance contributions are 72.8%, 72.8%, 76.4% and 84.7% respectively, and at a scan rate of 1.0 mV / s, the capacitance contribution rate reaches 88.9%. These results indicate that the excellent battery capacity of Mo-ReS2@C / CF mainly comes from the capacitance control behavior.
[0097] Fig.15 The discharge cycle curves of potassium ion batteries prepared in Comparative Example 2 (ReS2), Comparative Example 6 (Mo-ReS2@C) and Example 2 (Mo-ReS2@C / CF) of the present invention at current densities of 0.05, 0.1, 0.2, 0.5 and 1A / g are shown in the following figure. The voltage range of the test is 0.01-3V. Mo-ReS2@C / CF shows higher specific capacity than Mo-ReS2@C and ReS2 at current densities of 0.05, 0.1, 0.2, 0.5 and 1A·g. -1At the current density, the capacity of Mo-ReS2@C / CF electrode can reach 627, 554, 491, 365 and 263 mAh·g, respectively. -1 The discharge capacity is much higher than that of ReS2 and Mo-ReS2@C tested under the same conditions. -1 At this current density, the discharge capacity of ReS2 is already 0, and the discharge capacity of Mo-ReS2@C is only 53.74 mAh·g -1 , indicating that the Mo-ReS2@C / CF negative electrode material has strong rate performance.
[0098] Fig.16 The discharge cycle curves of potassium ion batteries prepared in Comparative Example 2 (ReS2), Comparative Example 6 (Mo-ReS2@C), and Example 2 (Mo-ReS2@C / CF) at a current density of 0.5 A / g. At the same current density, Mo-ReS2@C / CF exhibits a higher specific capacity. -1 At a current density of 2.547 W / m, Mo-ReS2@C / CF remained stable for 143 cycles, and the coulombic efficiency was almost maintained at 100%. Compared with Mo-ReS2@C, the good cycle stability of Mo-ReS2@C / CF material can be attributed to the effective inhibition of the volume expansion of the thin layer ReS2 material by CF during the charge and discharge process, and the overall conductivity, rate performance and cycle stability of the material are improved.
[0099] In summary, in order to address the problem of ReS2's easy pulverization and low conductivity during the charging and discharging process, ReS2 nanosheets were doped with Mo, C, and N and grown on a flexible three-dimensional carbonized foam (CF) skeleton to obtain a Mo-ReS2@C / CF composite material with good conductivity, rich active sites, and stable structure. In this material, the "bottom-up" multi-synergistic doping of Mo, C, and N at the anion and cation atomic level effectively improves the electronic conductivity of layered sulfide materials such as ReS2, and the in-situ growth on the flexible matrix CF with good conductivity provides more active sites for ion deintercalation. At the same time, the volume change of the three-dimensional carbonized foam (CF) buffer material during the charging and discharging process enhances the reversible capacity and cycle stability of the material, so that the Mo-ReS2@C / CF negative electrode material exhibits excellent sodium or potassium storage performance, thereby improving the electrochemical properties of sodium ion batteries (SIBs) and potassium ion batteries (KIBs) such as rate performance and cycle stability.
[0100] The above are only specific embodiments of the present invention, but the technical features of the present invention are not limited thereto. Any simple changes, equivalent replacements or modifications made based on the present invention to solve basically the same technical problems and achieve basically the same technical effects are all included in the protection scope of the present invention.
Claims
1. A method for preparing a carbonized foamed layered sulfide negative electrode material, characterized in that: The carbonized foam obtained by high-temperature carbonization of the foam is mixed with ammonium perrhenate, thiourea, hydroxylamine hydrochloride, ammonium molybdate tetrahydrate, polyvinyl pyrrolidone, and deionized water to undergo hydrothermal reaction to obtain a Mo-ReS2@PVP / CF composite material. The Mo-ReS2@PVP / CF composite material is then placed in a tubular furnace for high-temperature carbonization to obtain a carbonized foam flexible self-supporting layered sulfide negative electrode material Mo-ReS2@C / CF. The specific process steps are as follows: Step 1, preparation of carbonized foam: place the melamine foam in a deionized water ultrasonic cleaning machine for cleaning for 25 to 30 minutes, then transfer it to an ethanol ultrasonic cleaning machine for cleaning for 20 to 25 minutes, dry the cleaned melamine foam and place it in a tubular furnace, heat it to 500 to 800 °C at a heating rate of 5 °C / min under an inert gas atmosphere, maintain it for 2 to 2.5 hours, and then cool it to obtain the carbonized foam; Step 2, preparation of Mo-ReS2@PVP / CF composite material: weigh 1.1-1.2 parts by weight of ammonium perrhenate, 1.3-1.4 parts by weight of thiourea, 0.8-0.9 parts by weight of hydroxylamine hydrochloride, 0.3-0.4 parts by weight of ammonium molybdate tetrahydrate, 0.3-0.4 parts by weight of polyvinyl pyrrolidone, and 195-200 parts by weight of deionized water, mix and stir for 15-18 min to obtain a uniformly dispersed precursor solution, add 30-32 pieces of carbonized foam to the precursor solution, continue to stir for 30-40 min to mix evenly, then transfer the mixed solution to a polytetrafluoroethylene reaction liner, and then place it in a stainless steel reactor, keep it warm in a forced air drying oven at 210-220°C for 16-18 h, then cool it naturally, and then wash it with deionized water and ethanol three times, centrifuge it, and then dry it in a vacuum drying oven at a temperature of 70-75°C for 8-10 h, cooled to room temperature to obtain Mo-ReS2@PVP / CF composite material; Step 3. Preparation of negative electrode material Mo-ReS2@C / CF: Place the Mo-ReS2@PVP / CF composite material prepared in step 2 in a tubular furnace, heat it to 700-710°C at a heating rate of 5°C / min under an inert gas atmosphere, and then maintain it for 2.0 h for high-temperature carbonization. After cooling, the negative electrode material Mo-ReS2@C / CF is obtained.
2. The method for preparing a carbonized foamed layered sulfide negative electrode material according to claim 1, characterized in that: The length, width and height of the melamine foam are 1.5-2 cm, 1.5-2 cm and 0.3-0.5 cm respectively.
3. The method for preparing a carbonized foamed layered sulfide negative electrode material according to claim 1, characterized in that: The frequency of the ultrasonic cleaning machine is 100-120 Hz, and the ethanol concentration is 95%.
4. The method for preparing a carbonized foamed layered sulfide negative electrode material according to claim 1, characterized in that: The inert gas is nitrogen or argon, and the standard concentration of nitrogen or argon is 99.99%.
5. Use of the carbonized foamed layered sulfide negative electrode material according to any one of claims 1 to 4 in an ion battery.
6. The use of the carbonized foamed layered sulfide negative electrode material in an ion battery according to claim 5, characterized in that: The ion battery is prepared by the following method: a CR2032 battery shell is selected, and the negative electrode shell, spring, gasket, reference electrode-metal sheet, diaphragm, flexible self-supporting Mo-ReS2@C / CF electrode, and positive electrode shell are assembled layer by layer in a specific order, 0.1 to 0.5 mL of sodium ion battery electrolyte or potassium ion battery electrolyte is added dropwise, and the battery is placed in a packaging machine for pressing to obtain a sodium ion battery or a potassium ion battery.
7. The use of the carbonized foamed layered sulfide negative electrode material in an ion battery according to claim 6, characterized in that: The electrolyte of the sodium ion battery is composed of sodium perchlorate, ethylene carbonate, diethyl carbonate, and fluoroethylene carbonate. The concentration of sodium perchlorate is 1 to 1.2 mol / L, the weight ratio of ethylene carbonate to diethyl carbonate is 1:1, and the concentration of fluoroethylene carbonate is 5 to 5.5%.
8. The use of the carbonized foamed layered sulfide negative electrode material in an ion battery according to claim 6, characterized in that: The potassium ion battery electrolyte is composed of potassium fluorosilicate, ethylene carbonate and diethyl carbonate. The concentration of potassium fluorosilicate is 0.8-0.9 mol / L, and the weight ratio of ethylene carbonate to diethyl carbonate is 1:
1.
9. The use of the carbonized foamed layered sulfide negative electrode material in an ion battery according to claim 6, characterized in that: The metal sheet is a 12mm metal sodium sheet or metal potassium sheet. The preparation of the ion battery is carried out in a water-free and oxygen-free glove box. The water and oxygen concentrations in the glove box are H2O<0.01ppm and O2<0.01ppm.
Citation Information
Patent Citations
High-performance indoor-temperature sodium ion battery and preparation method thereof
CN105514425A
Preparation method of two-dimensional nanomaterial
CN105668530A
Flexible self-supporting ternary metal sulfide / carbon foam composite electrode material for energy storage device
CN109216038A
Flexible self-supporting composite material and preparation method thereof and application thereof
CN109728268A
Self-supporting SiOx-based composite negative electrode material and preparation method thereof
CN109980198A
